2000
DOI: 10.1046/j.1365-2958.2000.01795.x
|View full text |Cite
|
Sign up to set email alerts
|

cis‐Acting regulatory sequences for antitermination in the transcript of the Bacillus subtilis hut operon and histidine‐dependent binding of HutP to the transcript containing the regulatory sequences

Abstract: SummaryThe location of the cis-acting regulatory region for histidine-dependent antitermination of the Bacillus subtilis hut operon was determined. A secondary structure, whose sequences partially overlap with the downstream terminator, was found in the regulatory region of the hut transcript. Mutational analysis of the regulatory region showed that the secondary structure was required for histidine-dependent antitermination. An electrophoretic mobility-shift assay demonstrated that, in response to the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 41 publications
(73 reference statements)
1
34
0
Order By: Relevance
“…It follows that in cases of nutrient limitation leading to a drop in GTP in the cell, CodY repression is alleviated, allowing the expression of many genes involved in cell adaptation to this poorer environmental condition. Many CodY-dependent genes are also regulated by additional mechanisms, allowing their control in response to other environmental factors (Brandenburg et al, 2002;Debarbouille et al, 1999;Ferson et al, 1996;Kim et al, 2003;Mader et al, 2004;Mirel et al, 2000;Nakano et al, 1991;Oda et al, 2000;Ogura et al, 2001;Wray et al, 1997;Yoshida et al, 2003). In B. subtilis, CodY has been shown to directly interact with, in addition to GTP, BCAA, in particular isoleucine (Shivers & Sonenshein, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It follows that in cases of nutrient limitation leading to a drop in GTP in the cell, CodY repression is alleviated, allowing the expression of many genes involved in cell adaptation to this poorer environmental condition. Many CodY-dependent genes are also regulated by additional mechanisms, allowing their control in response to other environmental factors (Brandenburg et al, 2002;Debarbouille et al, 1999;Ferson et al, 1996;Kim et al, 2003;Mader et al, 2004;Mirel et al, 2000;Nakano et al, 1991;Oda et al, 2000;Ogura et al, 2001;Wray et al, 1997;Yoshida et al, 2003). In B. subtilis, CodY has been shown to directly interact with, in addition to GTP, BCAA, in particular isoleucine (Shivers & Sonenshein, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…hut mRNA appears to form a stable terminator structure (+498 to 572) in the absence of activated HutP, whereas the region between +489 to +537 seems to form a destabilized RNA structure (ribonucleic anti-terminator, RAT) upon binding to the activated HutP [30]. Our biochemical [30] and recent structural studies [28] revealed that HutP forms a hexamer, as a trimer of dimers. Based on these results, a search was made for repeated sequences within the minimal 79-mer RAT element, and found three UAG repeats that are each separated by a 4-nucleotide spacer region.…”
Section: Characterization Of Hut Mrnamentioning
confidence: 60%
“…hut mRNA appears to form two alternative secondary structures that depend upon the presence of activated HutP [30]. The regions that fold into alternative structures are located in between +489 to +572 of hut mRNA (Fig.…”
Section: Characterization Of Hut Mrnamentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous analyses suggested that the HutP protein binds to its cognate RNA only in the presence of L-histidine [28,30]. To analyze the ability of HutP to bind to the mRNA, the reactions are carried out in the presence of L-histidine (10 mM) and Mg 2+ ions (10 mM).…”
Section: Requirement Of Divalent Metal Ionsmentioning
confidence: 99%